THE EFFECT OF PROFITABILITY, LIQUIDITY, LEVERAGE, GROWTH AND MEASUREMENT OF COMPANIES ON DEVIDENT POLICY ON MANUFACTURING COMPANY THAT REGISTERED ON IDX 2014-2016 - Junita, Rahel (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to analyze the influence of profitability, liquidity, leverage, growth, and firm size on dividend policy (An Empirical Study on Manufacture Companies listed in the Indonesia Stock Exchange in the period of 2014-2016). The research is used causal correlation method. The population was 119 manufacture companies listed in BEI in the period of 2014-2016, but only 109 of them have the criteria as the samples, taken by using census sampling technique. There were 327 observations within 3 years of the research period. The data were gathered by the study document and analyzed by using multiple linear regression analysis. The result of the research shows that profitability, liquidity, leverage, growth, and firm size have significant influence on dividend policy. Partially, profitability, liquidity, and growth have positive and significant influence on dividend policy, while leverage and firm size have negative and insignificant influence on dividend policy.